COMPARISON OF CULTURAL VALUES IN THE NOVEL TENGGELAMNYA KAPAL VAN DER WIJCK BY BUYA HAMKA AND THE NOVEL TANAH PARA BANDIT BY TERE LIYE (SOCIOLOGICAL STUDY OF LITERATURE) - Nopiyanti, Nopiyanti; Kamiri, Kamiri; Anggraini, Nori (Jurnal Dinamika UMT, 2023)
Obtained are based on the formulation, objectives, results, and discussion in the analysis of cultural values in the novel Tenggelamnya Kapal Van Der Wijck by Buya Hamka and Novel Tanah Para Bandit by Tere Liye previously stated, described as follows. The results of the analysis of cultural values in the novel The Sinking of the Van Der Wijck Ship by Buya Hamka and the novel Tanah Para Bandits by tere Liye contain 79 data. The data obtained is divided into cultural values in human relations with God, cultural values in human relations with nature, cultural values in human relations with society, cultural values in human relations with others, and cultural values in human relations with oneself.